2022
DOI: 10.21203/rs.3.rs-1794353/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lost to Follow-Up and Its Predictors among Human Immune Deficiency Virus Infected Children on Antiretroviral Therapy, Southern Oromia, and Ethiopia: A Five Year Retrospective Cohort Study

Abstract: Background Lost to follow-up among pediatric human immune deficiency virus infected patients is a major challenge for the global scale-up of lifesaving antiretroviral therapy (ART). It is considerable obstacle for effectiveness of the program which negatively impacted on immunological benefits of ART and drug adherence. Additionally, it increases drug toxicity, resistance and acquired immune deficiency syndrome related morbidity and mortality. Therefore, it is very crucial to identify the incidence and determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…In Ethiopia, there is a paucity of evidence regarding the national incidence of LTFU among HIV-positive children on ART. Moreover, previous primary studies also confirmed that the incidence of LTFU among HIV-positive children on ART varied across regions in Ethiopia [13][14][15][16][17][18][19][20][21], ranging from 3.3 per 100 child years in the Oromia region [21] to 6.3 per 100 child years in the Amhara region [15]. Conducting an aggregated study using those primary studies is important to know about the national burden of LTFU among HIV-positive children on…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In Ethiopia, there is a paucity of evidence regarding the national incidence of LTFU among HIV-positive children on ART. Moreover, previous primary studies also confirmed that the incidence of LTFU among HIV-positive children on ART varied across regions in Ethiopia [13][14][15][16][17][18][19][20][21], ranging from 3.3 per 100 child years in the Oromia region [21] to 6.3 per 100 child years in the Amhara region [15]. Conducting an aggregated study using those primary studies is important to know about the national burden of LTFU among HIV-positive children on…”
Section: Introductionmentioning
confidence: 84%
“…The rest 107 articles were assessed by reviewing the full text. Finally, twenty-four studies were eligible and incorporated in the final analysis (Fig 1) [13][14][15][16][17][18][19][20][21][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. All studies were conducted using the cohort study design.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation